PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM – ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SD NEGERI 009 PERKEBUNAN SUNGAI PARIT - Salbiyah, Salbiyah; Alpusari, Mahmud; Daud, Damanhuri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstraction: This research is conducted by the low student’ achievement in social lesson, with the average classscore is 63,42. Whereas minimum criteria passing grade of the social is 70.Among the number of the student is 19 and only 7 students’ from them reach KKM with the classical completeness 36,84%. The formulation of the problem: “is the implementation of Corporative Model of learning type STAD can Increase Student Achievement in Social for Five Grades Student of Public Elementary School 009 Perkebunan Sungai Parit, Sungai Lala. In social lesson by five grade student of public Elementary School 009 Perkebunan Sungai Parit, Sungai Lala Sub district Indragiri Hulu Regency?”. This research goal is to increase the study achievement in Social lesson by five grade student of public Elementary School 009 Perkebunan Sungai Parit, Sungai Lala Sub district Indragiri Hulu regency with the Implementation of Corporative Model of Learning type STAD. This research was conducted in 10th March 2015 until 20th March 2015 with two phases, The Subject of this research is the students of public Elementary School 009 Perkebunan Sungai Parit with 19 students become a data sources. This research is they Classroom Action Research (PTK) . Classroom action Research is a research that is conducted due to they problem a rise in the class. The instrument Collecting Data in this thesis is Syllabus, Lesson Plan (RPP) and students work sheet (LKS). This thesis showed the students achievement which is gained from they daily examination before action with average score is 63,42% and increase in first phase with average 71,29% and second phase become 78,82%. Teacher activities in teaching learning process in first phase is 62,5% and at the second phase is 79,16%. In the second phase in the first meeting 87,5% and second meeting becomes 95,83%. The result of the rescarch in class V of public Elementary School 009 Perkebunan Sungai Parit gave evidence that the Implementation of Cooperative Learning Model type STAD can increase the students achievement of Sosial Lesson in five grade students of Public Elementary School 009 Perkebunan Sungai Parit.The use of Cooperative Learning Model type STAD can increase the students’ achievement and can be one of the alternative choices to increase teaching and learning process.Key word: Cooperative Learning Model type STAD, Outcome IPS